Pelatihan dan Sosialisasi Peraturan Pemerintah Nomor 55 Tahun 2022 Tentang Penyesuaian Pengaturan Dibidang Pajak Penghasilan Bagi UMKM di Kabupaten Bengkalis - Alfiati Silfi; Meilda Wiguna; Eka Hariyani; Nita Wahyuni; Rosmayani Rosmayani (PELANTAR PRESS, 2025)
This community service activity aims to enhance the understanding of Micro, Small, and Medium Enterprises (MSMEs) in Bengkalis Regency regarding the new provisions of Government Regulation Number 55 of 2022 on the Adjustment of Income Tax Regulations. This regulation introduces significant changes to the taxation mechanisms and rates for MSMEs, making it essential for business actors to receive accurate information and guidance. The activity was carried out through training sessions, socialization, and interactive discussions involving 25 MSME participants. The materials covered included MSME tax obligations, changes in tax rates and reporting procedures, and strategies for effective tax compliance. The results showed an increase in participants’ knowledge of the new tax regulations, as indicated by pre-test and post-test scores and the high level of engagement during the QA sessions. This activity is expected to encourage better tax compliance, increase tax contributions from the MSME sector, and strengthen the synergy between business actors and local governments in achieving transparent and fair tax governance